Digital Materials: China and Japan. (Religious Studies Review (John Wiley & Sons, Inc.), 2022)
The article reviews several websites including "The Religious Studies Project" located at https://www.religiousstudiesproject.com/; "Religion and Politics" located at www.religionandpolitics.org; and "Sociology of Religion Resources" located at https://www.sociologyofreligion.net.